Public environmental perception and behavior intention on garden showcase design in Putrajaya - Ibrahim, Nora (2016)
There is a large variety of different types of tourist attractions and festivals, as short- term events have a vast impact on the public. Since the significance of the festival is to educate the public and open up opportunities for them to achieve its vision, the organizer, Putrajaya Cooperation had taken steps to hold a Flower and Garden Festival to achieve its ambition to develop Putrajaya as a “Garden City”. To achieve this, the organizer together with local residents and visitors from outside the city participated in the event. The organizer had provided a wide range of garden designs to enhance the knowledge and ideas to attract visitors to build their own garden. This indirect impact not only changes the behavior of the visitors but was also important to the organizer in achieving their vision to develop Putrajaya as a “Garden City”. However, not many research was conducted on the garden festival and their impact on the visitors’ behaviour intention after visiting the festival. Therefore, the present study examined how the garden festival gave an impact to the visitors' behavior through their satisfaction on the variety of designs and ideas in the garden showcase. Besides this study explored how emotion engendered through the garden showcase which influenced the visitors' psychological attachment after visiting the showcase. A survey was conducted on the visitors of the Royal FLORIA Putrajaya 2015 by using self-administered questionnaires. A total of 428 respondents were involved in this study. From the analysis, the Confirmatory Factor Analysis (CFA) was conducted to obtain the 3-factor solutions using the AMOS software. The result showed that the value of Cronbach Alpha was higher than 0.70. The results of the CFA confirmed that the data was suitable for the model. The study also proved that satisfaction mediated the relationship between the perceived value of the garden showcase and the behavioral intention. It was found that satisfaction played the intervening role in influencing the visitors’ behavior intention to build and own a garden which they will recommend to others. The findings of this study also provided that satisfaction had a mechanism in the behavioral change by building their own garden and recommend to others thus, this indirectly achieved the vision of the organizer to be a Garden City.